Residents’ perceptions of the tourism impacts on a mature destination: The case of Madeira Island - Teixeira, Diogo (2019)
Residents play a fundamental role in the quality of tourists’ experiences and satisfaction derived from a visit and, thus, in the success of a tourism destination. This paper addresses the perceptions that residents have the impacts of tourism on Madeira Island, a mature tourism destination. Based on data extracted from a survey administered to residents during August and September 2018, we inquired on the extent to which they maintain a positive perception of the impacts of the tourist industry. The survey tried to address the residents’ perceptions of economic, cultural, social, or environmental impacts. In the analysis of the data, both descriptive and multivariable statistical methods were used. The empirical results attained indicate that residents feel that there is no excess of tourism on the island. They do not fail to realize that there are a few negative consequences, but the positive ones got better scores on average. Being an inhabitant of an urban or a rural site did not seem to influence differently the perceptions gathered on the contribution of tourism to the overall development of Madeira Island. This type of analysis can serve as a useful tool for tourism planners and managers in order to prevent or minimize eventual negative impacts of the tourism industry as felt by the local inhabitants and, thus, for creating the required policies.